School Principals’ Perceptions of Curriculum Reform: A Case Study in Central Java - Soedjono Soedjono; Senowarsito Senowarsito; Harto Nuroso; Lasminto Lasminto; Rizki Fauzan; Hansen Lutfiartha (STAI Hubbulwathan Duri, 2025)
The implementation of Kurikulum Merdeka in Indonesia emphasizes curriculum adaptation based on students’ needs, institutional characteristics, and local contexts. Key mediating principles—focus, alignment, and flexibility—guide curriculum execution across classroom, school, district, and national levels. This study investigates school principals’ perceptions of these principles and explores their mediation strategies in preparing for curriculum implementation.This qualitative exploratory case study involved nine purposively selected principals from elementary, junior high, and senior high schools in three residencies of Central Java (Semarang, Pati, and Pekalongan). Data were collected through semi-structured interviews and document analysis, then analyzed using Miles and Huberman’s interactive model. Triangulation, member checking, and expert validation were employed to ensure credibility and trustworthiness.Principals demonstrated positive perceptions of the Kurikulum Merdeka’s mediating principles. At the classroom level, strategies focused on student-centered learning and literacy activities. At the school level, internal collaboration and professional learning communities supported alignment with local needs. District-level mediation involved cooperation with education offices and stakeholder forums. At the national level, principals simplified policy directives through infographics and digital media. Curriculum leadership played a central role in aligning policy with practice.The study highlights how curriculum leadership facilitates the integration of national policies into local school contexts through multi-level mediation strategies. Differences in implementation were noted across school levels, particularly in stakeholder engagement and assessment practices.To ensure sustainable and contextual implementation of Kurikulum Merdeka, targeted curriculum leadership training—especially for elementary school principals—is recommended.